One-pot construction of three dimensional CoMoO4/Co3O4 hybrid nanostructures and their application in supercapacitors. Issue 42 (25th September 2015) - Zhou, Min; Lu, Fei; Shen, Xiaoshuang; Xia, Weiwei; He, Hui; Zeng, Xianghua
Abstract : Three dimensional CoMoO4 /Co3 O4 hybrid nanostructures were synthesized via one-pot hydrothermal method and displayed excellent performance as electrode material in supercapacitors. Abstract : A facile one-pot hydrothermal method was developed to synthesize a CoMoO4 /Co3 O4 hybrid nanostructure where CoMoO4 nanosheets were supported by a hierarchical framework assembled by Co3 O4 nanorods. The morphology and structure of this three dimensional nanocomposite were characterized in detail and a rational growth mechanism was proposed based on them. The unique structural features of our CoMoO4 /Co3 O4 hierarchical nanohybrid allow for high specific surface and multiple faradaic redox reactions for electrode materials of supercapacitors. Consequently, a high specific capacitance (1062.5 F g −1 at the current density of 1 A g −1 ) and an excellent cyclic performance (90.38% of the initial capacitance retained after 2000 cycles at a current density of 20 A g −1 ) were obtained. In addition, an asymmetric supercapacitor with high energy density of 31.64 W h kg −1 was achieved at a power density of 7270 W kg −1 . This work thus provides an excellent candidate for high-performance supercapacitor fabrication.